Inclusive innovation ecosystems and township-based startups in South Africa - Mhlanga, Thandeka Innocentia (University of the Witwatersrand, Johannesburg, 2024)
In South Africa, the apartheid legacy gave rise to inequality and marginalised communities. To date, the country has the highest inequality income distribution in 2021 globally, with a GINI score of 63 (Dyvik, 2024). The score measures the income inequality in a country, and the closer it is to zero, the more equally distributed the income. Inequality is said to be inherently problematic and holds back social and economic development in the long run (Stiglitz, 2012). Harsh et al. (2018) explores the overlaps between the levels of inclusive innovation and three pathways for increasing equality through emerging technologies frameworks, with a focus on the inclusiveness of the innovation policy for nanotechnology, the development of nanotechnology, and its impact on the marginalised communities in South Africa. Inclusive innovation can potentially redress the inequality challenges brought by the apartheid regime. New technology-based firms are essential as they are regarded as economic game changers in that they embrace continuous technological changes and play a key role in creating and commercializing new products, processes, and technologies in our societies. Particularly in South Africa, they are considered a key role player in addressing political issues such as inequality that emerged during the apartheid era, and that is redressed through the black economic empowerment (BEE) policies (Ndabeni, 2008). As a result, they are not only a source of new employment contributing towards the gross domestic product (GDP), but they are also instrumental in creating new industries such as personal computers, genetic engineering, machine vision, and robotics (Almus & Nerlinger, 1999; Kazanjian, 1988). iii By applying the inclusive innovation ladder and the innovation ecosystem framework, this study evaluates the inclusiveness of The Innovation Hub’s eKasiLab programme, which the local innovation ecosystem enabled to develop and support the growth of township-based innovators.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the Energy Leadership to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Inclusive innovation; Innovation ecosystem; eKasiLab; Township-based innovators; The Innovation Hub; UCTD; SDG-9: Industry, innovation and infrastructure